Path analysis of skin cancer preventive behavior among the rural women based on protection motivation theory - Nasrin Roozbahani; Abdol-Hossain Kaviani; Mahboobeh Khorsandi (BMC, 2020)
Abstract Background Determining the effective factors on the adoption of preventive behaviors capable of reducing the risk of skin cancer is an important step in designing interventions to promote these behaviors. Based on the protection motivation theory, the present study is aimed to conduct a path analysis of skin cancer preventive behaviors in rural women to explore these factors. Methods In this cross-sectional study, 243 rural women were randomly selected from the west of Iran to receive a valid and reliable questionnaire assessing constructs from the protection motivation theory, as well as demographic information. Fully completed questionnaires were returned by 230 women and the data were analyzed by SPSS 22 and LISREL8.8. Results Concerning skin cancer preventive behaviors, 27.8% of women wore sun-blocking clothing when working under the sun, 21.7% used sunscreen cream, 5.7% wore a cap, and 4.8% used gloves and sunglasses. Protection motivation theory and per capita income explained 51% of motivation variance and 25% of the variance of skin cancer preventive behaviors. The response efficacy construct was the strongest predictor of the motivation of protection (ß = − 0.44, p < 0/001). Per-capita income (ß = − 0.34, p < 0/001) and motivation (ß = − 0.33, p < 0/001) were the strongest predictors of these behaviors. Conclusions This study showed that protection motivation theory is efficient in predicting skin cancer preventive behaviors and the interventions can be designed and implemented by this theory. Proper planning is also necessary for promoting these behaviors among people with low per-capita income.